Metode Tahsin dalam Memperbaiki Bacaan Al-Quran - Erliani Siagian; Zailani Zailani (-, 2021)
This research is motivated by the problem of the lack of understanding of some students at Mts madinatussalam, Medan on the importance of pronouncing makharijul letters and correct recitation when reading the Qur'an. Some of the students accustomed to listening to the teacher's explanation without repeating back home. Plus for some new students I've never entered this school at all study Tajweed. Therefore, the researchers considered it necessary share the learning of tahsin in order to increase understanding of students so that they are able to read the Qur'an with good and right. The definition of Tahsin itself is to recite or pronounce and remove each letter of the Qur'an from its place by giving it its rights correctly. Or perfecting things related to the perfection of the pronunciation of the letters of the Qur'an from the aspect of their properties that are always attached to them and perfecting the pronunciation of the law of the relationship between one letter and another such as idzhar, idgham, ikhfa and so on. The research this time used qualitative data analysis techniques. This research was conducted for 10 days. With a meeting for one hour every day at 10:00 to 11:00 WIB. With the holding of the tahsin learning program for students, it shows an increase in the reading ability of students who are starting to improve. Therefore, this kind of activity is expected to be sustainable.